Land‐Air Exchanges of Various Gaseous Nitrogen Species in an Urban Wetland Based on In Situ Flux Observations - Qian Yu; Zimeng Zhang; Piaopiao Ke; Jiale Chang; Han Li; Wenjia Wang; Lei Duan; Ronghua Kang; Lei Zhang; Yu Zhao (Geophysical Research Letters)
Abstract Wetlands are universally recognized as hotspots for nitrogen cycling and gaseous nitrogen emissions. In this study, the fluxes of nitric oxide (NO), nitrogen dioxide (NO2), ammonia (NH3), and nitrous oxide (N2O) were observed seasonally in the mud and waterfront plots of an urban wetland in eastern China using a dynamic flux chamber. The results revealed that the fluxes of NO, NO2, and NH3 displayed a diurnal pattern of higher values during the day and lower values at night, which was opposite to that of N2O. The average annual emissions of NO, NH3, and N2O were 0.16 ± 0.04, 0.59 ± 0.03, and 8.81 ± 0.44 kg N ha−1 yr−1, respectively. Conversely, NO2 exhibited deposition, with an annual flux of 1.51 ± 0.03 kg N ha−1 yr−1. Given the evolving area of urban wetlands, the emissions of gaseous nitrogen, particularly N2O, deserve substantial attention.